Term premia implications of macroeconomic regime changes - Giacomo Carboni (European Central Bank (ECB), 2014)
Term premia are shown to provide crucial information for discriminating among alternative sources of change in the economy, and namely shifts in the variance of structural shocks and in monetary policy. These sources have been identified as competing explanations for time-varying features of major industrial economies during the 80s and 90s. While hardly distinguishable through the lens of standard DSGE models, lower non-policy shock variances and tighter monetary policy regimes imply higher and lower term premia, respectively. As a result, moving to tighter monetary policy alone cannot explain the U.S. improved macroeconomic stability in the 80s and 90s: term premia would have shifted downwards, a fact inconsistent with the evidence of higher premia from early 80s onwards, where term premia are derived following Cochrane and Piazzesi (2005). Conversely, favourable shifts in non-policy innovation variance imply movements in term premia which are at least qualitatively consistent with historical patterns.
Keywords: E43; E52; 330; DSGE models; regime switching; term premia